Effectiveness of Hand Sanitizer Betel Leaf Extract in the Form of Spray And Gel as an Antiseptic Without Alcohol - Andrew Setiawan Rusdianto; Giyarto Giyarto; Zhelma Rahmatika; Thabed Tholib Baladraf; Winda Amilia (Jurnal Penelitian Tanaman Industri, 2021)
The use of hand sanitizers to maintain hand hygiene is a must in disease prevention. The addition of betel leaf extract is expected to increase the effectiveness of hand sanitizers in killing bacteria. The purpose of the study was to determine the effect of adding betel leaf extract on the effectiveness of hand sanitizer as a non-alcoholic antiseptic. The research was conducted at the Agroindustrial Technology and Management Laboratory and the Microbiology Laboratory of Food and Agricultural Products, Faculty of Agricultural Technology, University of Jember. This study used a Factorially Completely Randomized Design with two factors, namely concentration and preparation. This study used a factorial Complete Randomized Design with two factors, namely concentration and preparation. The treatments consist of A1B1 (addition of betel leaf extract 5% with gel preparation), A2B1 (addition of betel leaf extract 10% with gel preparation), A3B1 (addition of betel leaf extract 15% with gel preparation), A4B1 (addition of betel leaf extract 20 % with gel preparation), A1B1 (addition of betel leaf extract 5% with spray preparation), A1B2 (addition of 10% betel leaf extract with spray preparation), A1B3 (addition of 15% betel leaf extract with spray preparation), A1B4 (addition of betel leaf extract) betel 20% with spray preparations). Parameters observed were pH, antiseptic power, and organoleptic (color, odour, and shape). The result showed that the addition 5-20% of betel leaf extract in gel preparations and 5-15% in spray preparations are ineffective and does not comply with SNI requirements. Meanwhile, the addition of betel leaf extract in spray preparations with a concentration of 20% is effective as a natural antiseptic with a pH of 5.8 and an antibacterial of 2 colonies so that it complies with Indonesian National Standard.Keywords:   antibacterial, colony, organoleptic AbstrakEFEKTIVITAS HAND SANITIZER EKSTRAK DAUN SIRIH BENTUK SPRAY DAN GEL SEBAGAI ANTISEPTIK TANPA ALKOHOLPenggunaan hand sanitizer untuk menjaga kebersihan tangan merupakan salah satu keharusan dalam pencegahan penyakit. Penambahan ekstrak daun sirih diharapkan dapat menambah efektifitas hand sanitizer dalam membunuh bakteri. Tujuan penelitian adalah mengetahui pengaruh penambahan ekstrak daun sirih terhadap efektifitas hand sanitizer sebagai antiseptik tanpa alkohol. Penelitian dilaksanakan di Laboratorium Teknologi dan Manajemen Agroindustri dan Laboratorium Mikrobiologi Pangan dan Hasil Pertanian, Fakultas Teknologi Pertanian Universitas Jember. Penelitian ini menggunakan Rancangan Acak Lengkap faktorial dua faktor yaitu konsentrasi ekstrak daun sirih dan sediaan. Kombinasi perlakuan terdiri dari A1B1 (penambahan ekstrak daun sirih 5% dengan sediaan gel), A2B1 (penambahan ekstrak daun sirih 10% dengan sediaan gel), A3B1 (penambahan ekstrak daun sirih 15% dengan sediaan gel), A4B1 (penambahan ekstrak daun sirih 20% dengan sediaan gel), A1B1 (penambahan ekstrak daun sirih 5% dengan sediaan spray), A1B2 (penambahan ekstrak daun sirih 10% dengan sediaan spray), A1B3 (penambahan ekstrak daun sirih 15% dengan sediaan spray), A1B4 (penambahan ekstrak daun sirih 20% dengan sediaan spray). Parameter yang diamati yaitu pH, daya antiseptik, dan organoleptik (warna, bau dan bentuk). Hasil penelitian menunjukkan penambahan ekstrak daun sirih 5-20% pada sediaan gel dan 5-15% pada sediaan spray tidak efektif dan tidak sesuai Standar Nasional Indonesia (SNI). Penambahan ekstrak daun sirih 20% pada sediaan spray efektif digunakan sebagai antiseptik tanpa alkohol dengan pH 5,8 dan antibakteri 2 koloni sehingga sesuai standar SNI.Kata kunci : antibakteri, koloni, organoleptik